1993
DOI: 10.1093/jac/32.suppl_b.133
|View full text |Cite
|
Sign up to set email alerts
|

A non-comparative, multicentre study of cefepime in the treatment of serious bacterial infections

Abstract: Multi-resistant strains of Gram-negative bacteria are rapidly emerging as a frequent cause of serious bacterial infection in the hospital environment. Effective treatment must include an antibiotic with activity against these organisms. In an open multicentre study, cefepime was evaluated as empirical therapy in 156 hospitalized patients (mean age 57 years) with serious infection of the urinary tract (n = 43), lower respiratory tract (n = 101) and skin and soft tissue (n = 12). In 18 patients, septicaemia/bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Both compounds are structurally similar except for a methyl-pyrrolidino group that gives the cefepime molecule a zwitterionic configuration [17]. This offers cefepime an apparent chemical advantage of enhanced bactericidal activity by rapid penetration of the porin channels in the outer membrane of Gram-negative bacteria [18,19].…”
Section: Cefepime and Ceftazidime: Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…Both compounds are structurally similar except for a methyl-pyrrolidino group that gives the cefepime molecule a zwitterionic configuration [17]. This offers cefepime an apparent chemical advantage of enhanced bactericidal activity by rapid penetration of the porin channels in the outer membrane of Gram-negative bacteria [18,19].…”
Section: Cefepime and Ceftazidime: Generalmentioning
confidence: 99%
“…Cefepime is active against Enterobacter spp., especially ceftazidime-resistant Enterobacter aerogenes [18], and has broadened antipseudomonal activity. Kieft et al [27] compared cefepime with ceftazidime as initial therapy for patients with sepsis syndrome due to serious bacterial infections in 114 patients.…”
Section: Gram-negative Activitymentioning
confidence: 99%
“…The fourth‐generation cephalosporins, with their broad antibacterial spectrum, would be an attractive therapeutic alternative, administered empirically, either as monotherapy or as part of a combination regimen. Initial studies utilizing fourth‐generation cephalosporins in patients suffering from severe nosocomial pneumonia in the ICU are encouraging 52,53. Cefpirome is one of the most potent β‐lactam antibiotics against penicillin‐resistant pneumococci and staphylococci 15,26,27,74 and should be useful for the treatment of hospitalized patients with severe, community‐acquired pneumonia or early‐onset nosocomial pneumonia.…”
Section: Resultsmentioning
confidence: 99%
“…Cefepime 2 g bid has also been shown to be effective in the treatment of severe community‐acquired or nosocomial pneumonia 52,53. In a comparative study, a satisfactory response was reported in 75% of the cefepime patients and 74% of patients receiving ceftazidime or cefotaxime 2 g tid 53.…”
Section: Severe Infectionsmentioning
confidence: 99%
“…A larger and more recent multicenter study compared the efficacy and safety of cefpirome and ceftazidime, either as monotherapy or in combination, with an aminoglycoside or metronidazole in the empiric treatment of 400 patients with nosocomial and community‐acquired pneumonia in the ICU 94, Clinical failure rates at the end of treatment were 34% vs 36% for cefpirome bid and ceftazidime tid, respectively, with no difference in outcome between monotherapy and combination therapy. In a non‐comparative study, a satisfactory clinical response was obtained in 89% of patients receiving cefepime bid 95. Based on these studies, it can be assumed that fourth‐generation cephalosporins are good alternatives to other broad‐spectrum antibiotics for the treatment of nosocomial pneumonia.…”
Section: Empiric Treatmentmentioning
confidence: 99%